Bank Regulation in Singapore. Issue 2 (7th October 2015) - Hofmann, Christian
Abstract: This article discusses the most important principles of one of the most relevant financial markets in the world—Singapore. While little affected by the Global Financial Crisis, Singapore is currently reforming the regulatory framework for banks operating in its territory, both nationally and foreign headquartered. This contribution starts by providing some brief information on the structure of the Singaporean banking sector and its regulator, the Monetary Authority of Singapore. The main discussion focuses on the principles of bank regulation, especially in comparison to the rules of the Third Basel Accord (Basel III). This part is followed by the principles that apply to banks in crises and Singapore's role in cooperation with regulators from other jurisdictions. This last section includes an analysis of Singapore's willingness to participate in transnational efforts that seek to address the challenges resulting from the activities of global systemically important banks.